Empirical links between housing markets and economic resilience - Cournède, Boris (OECD Publishing, 2019)
Housing markets, which are large and subject to sharp swings, shape to a great extent countries' exposure to economic crises and their capacity to recover from them. This paper analyses the transmission of housing-related shocks to the real economy: it investigates the role that policy plays in (a) mitigating or amplifying shocks and (b) facilitating or hampering a recovery. It considers macroprudential measures, rental regulation, taxation and land use restrictions. The aim is to investigate, which housing policy-related reforms can foster greater economic resilience. Among other results, it finds that a tighter macroprudential stance is generally linked to a lower likelihood of economic crisis and that higher effective rates of housing taxation are associated with smoother housing cycles
Keywords: Economics